Enhancers regulate 3′ end processing activity to control expression of alternative 3′UTR isoforms - Buki Kwon; Mervin M. Fansler; Neil D. Patel; Jihye Lee; Weirui Ma; Christine Mayr (Nature Communications, 2022)
Transcriptional enhancers are known to regulate transcript production. Here, the authors show that transcription factors that bind to enhancers also regulate polyadenylation site cleavage activity, thus changing expression of alternative 3’ UTRs.